Caregiver Burden of Rheumatoid Arthritis Patients With Self-Care Deficit in China: A Cross-Sectional Study - Guoxia HE,; Yu DING, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the level of caregiver burden of Chinese rheumatoid arthritis (RA) patients with self-care deficit. Patients and methods: This cross-sectional study included a total of 65 caregivers (30 males, 35 females; mean age 52 years; range 20 to 79 years) of 65 RA inpatients (9 males, 56 females; mean age 59 years; range 20 to 85 years) with self-care deficit. Demographic data of patients and their respective caregivers were collected. The level of caregiver burden was defined using Caregiver Burden Inventory, a 24-item-five-domain survey tool. Correlation between different demographic factors and caregiver burden was analyzed. Predictive factors for burden level were also investigated. Results: A mean Caregiver Burden Inventory score of 44.0±4.0 was observed among caregivers of Chinese RA patients with self-care deficit. Among the five Caregiver Burden Inventory domains, developmental burden scored the highest (11.7±1.4), while physical burden scored the lowest (6.7±1.0). Among various demographic factors, patients’ age (r=0.306, p=0.013) and health insurance coverage (r=-0.246, p=0.04) were correlated with the level of caregiver burden. Besides, caregiver’s educational level (r=-0.316, p=0.01), relationship of caregiver with the patient (r=0.355, p=0.004), and whether or not the caregiver lived with the patient (r=0.362, p=0.003) were also significant factors. Predictive factors for caregiver burden of RA patients were identified as patient’s health insurance coverage and caregiver’s relationship with the patient, in agreement with the correlation analysis. Conclusion: Since caregiver burden may contribute to adverse health outcomes, supportive interventions should be established to target Chinese RA patients with self-care deficit and their caregivers to consolidate the sustainable care provided both at hospital and home.